Familial diabetes predisposes PCOS patients to insulin resistance (IR), reproductive impairment and hepatic dysfunction: effects of d-chiro inositol (DCI) and alpha lipoic acid (ALA) administration on hepatic insulin extraction (HIE) index. (3rd August 2022) - Genazzani, Alessandro D.; Battipaglia, Christian; Petrillo, Tabatha; Piacquadio, Nicola; Ambrosetti, Fedora; Arnesano, Melania; Semprini, Elisa; Sponzilli, Alessandra; Tomatis, Veronica; Simoncini, Tommaso
Abstract: Objective PCOS is a syndrome is characterized by 2 out of 3 of the criteria established during the Rotterdam Consensus Conference. Recently the issue of insulin resistance (IR) has caught attention. Subjects A group of overweight/obese PCOS patients ( n = 30) have been evaluated before and after 3 months of daily integrative administration of d-chiro inositol (DCI) (500 mg) and alpha lipoic acid (ALA) (300 mg). Methods Hormonal and metabolic profiles, oral glucose tolerance test (OGTT) for glucose, insulin and C-peptide response were performed in baseline conditions and after DCI plus ALA treatment. Hepatic Insulin Extraction (HIE) index was computed along the OGTT to evaluate the liver ability in degrading insulin. Results The treatment decreased LH, Androstenedione (A), insulin plasma levels, BMI, HOMA index, AST and ALT. Considering patients for the presence ( n = 17) or absence of familial diabetes ( n = 13), the greatest improvements occurred in the former patients. Insulin response to OGTT was greatly reduced after the treatment interval in PCOS with familial diabetes. HIE computation disclosed that in presence of familial diabetes liver degradation of insulin is reduced thus leaving a higher amount of circulating insulin. DCI plus ALA administration decreased AST and ALT and restored hepatic insulin clearance since HIE profile was improved. Conclusion Our study demonstrates that in overweight/obese PCOS the predisposition to familial diabetes triggers IR not only through the endogenous impaired DCI and ALA synthesis but also through a reduced hepatic clearance of insulin. DCI plus ALA administration positively improved hormonal, metabolic profiles as well as liver function.